2002
DOI: 10.1037/0096-3445.131.3.424
|View full text |Cite
|
Sign up to set email alerts
|

What very small numbers mean.

Abstract: This article presents a theoretical and experimental framework for assessing the biases associated with the interpretation of numbers. This framework consists of having participants convert between different representations of quantities. These representations should include both variations in numerical labels that symbolize quantities and variations in displays in which quantity is inherent. Five experiments assessed how people convert between relative frequencies, decimals, and displays of dots that denote v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
27
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 48 publications
1
27
0
Order By: Relevance
“…Furthermore, Cohen et al (2002) has demonstrated that people's understanding of decimals are seemingly independent of their understanding of relative frequencies (e.g., 50 in 120). This reveals a close link between numerical format and quantity representation, at least in the case of decimals and relative frequencies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, Cohen et al (2002) has demonstrated that people's understanding of decimals are seemingly independent of their understanding of relative frequencies (e.g., 50 in 120). This reveals a close link between numerical format and quantity representation, at least in the case of decimals and relative frequencies.…”
Section: Discussionmentioning
confidence: 99%
“…It is therefore not unreasonable to assume that the mental representation of decimals is different from that of integers. My colleagues and I have previously demonstrated the uniqueness of decimal representation by revealing that the mental representation of decimals is different from and perhaps independent of the mental representation of relative frequencies (Cohen, Ferrell, & Johnson, 2002). In addition, there is some evidence that fractions are processed by the individual integer components, rather than the holistic proportion they represent (Bonato, Fabbri, Umilta, & Zorzi, 2007).…”
mentioning
confidence: 99%
“…1 is a simplified depiction of a strict Multiple Quantity Representation model (e.g., Cohen, 2009Cohen, , 2010Cohen, Ferrell, & Johnson, 2002;Gonzalez 1 Dehaene's (1992) Triple Code model assumes that the format modules link to one and other and each format module links to the same abstract representation. This architecture is a version of Seidenberg and McClelland's (1989) distributed model of word recognition.…”
Section: Introductionmentioning
confidence: 99%
“…For example, we did not examine risk-related comparisons, such as "Drug X does not require blood tests." Given our finding that introducing comparative benefit claims may influence beliefs about the risks of the drug, a direct comparison of riskrelated information would reveal whether the opposite would also be true, as suggested in previous research (Bowman, 2002;Cohen et al, 2002;Davis, 2007;Hoek, 2008;Kees et al, 2008).…”
Section: Discussionmentioning
confidence: 88%
“…Nonetheless, these findings illustrate the potential for comparative DTC ads to influence perceptions of the benefits and risk of advertised drugs, possibly leading consumers to magnify benefit and minimize risk. In fact, previous DTC research has consistently found that various DTC advertising strategies that increase perceptions of benefit also decrease perceptions of risk (Bowman, 2002;Cohen et al, 2002;Davis, 2007;Hoek, 2008;Kees et al, 2008). Consequently, a comparative claim that focuses on the superior effectiveness of a drug may also influence risk perceptions.…”
Section: Introductionmentioning
confidence: 89%